Cryphonectria naterciae: a new species in the Cryphonectria-Endothia complex and diagnostic molecular markers based on microsatellite-primed PCR. - Bragança, Helena; Rigling, Daniel; Diogo, Eugénio; Capelo, Jorge; Phillips, Alan; Tenreiro, Rogério (Fungal biology, 2011)
In a recent study intended to assess the distribution of Cryphonectria parasitica in Portugal, 22 morphologically atypical orange isolates were collected in the Midwestern regions. Eleven isolates were recovered from Castanea sativa, in areas severely affected by chestnut blight and eleven isolates from Quercus suber in areas with cork oak decline. These isolates were compared with known C. parasitica and Cryphonectria radicalis isolates using an integrated approach comprising morphological and molecular methods. Morphologically the atypical isolates were more similar to C. radicalis than to C. parasitica. Phylogenetic analyses based on internal transcribed spacer (ITS) and β-tubulin sequence data grouped the isolates in a well-supported clade separate from C. radicalis. Combining morphological, cultural, and molecular data Cryphonectria naterciae is newly described in the Cryphonectria-Endothia complex. Microsatellite-primed PCR fingerprinting with (GACA)(4) primer discriminated between C. naterciae, C. radicalis, and C. parasitica.
The following values have no corresponding Zotero field: accession-num: 21872182
Keywords: Ascomycota; Ascomycota: classification; Ascomycota: genetics; Ascomycota: isolation & purification; Chestnut tree; Cork oak tree; Cryphonectria parasitica; Cryphonectria radicalis (GACA)4; DNA; DNA Primers; DNA Primers: genetics; Endothiella gyrosa; Fagaceae; Fagaceae: microbiology; Fungal; Fungal Proteins; Fungal Proteins: genetics; Fungal: genetics; Microsatellite Repeats; Molecular Sequence Data; MSP-PCR; Mycological Typing Techniques; Mycological Typing Techniques: methods; phylogeny; Plant Diseases; Plant Diseases: microbiology; Polymerase Chain Reaction; Polymerase Chain Reaction: methods; Quercus; Quercus: microbiology; RFLP-PCR; Tubulin; Tubulin: genetics